Chain-mediating effect of interaction between telomeres and mitochondria under oxidative stress in coke oven workers - Gu, Zhiguang; Niu, Zeming; Yan, Zhaofan; Fan, Yahui; Sun, Jing; Zhao, Xiangkai; Duan, Xiaoran; Yao, Wu; Yang, Yongli; Wang, Wei (Environmental pollution (1987), 2023)
Coke oven emissions (COEs) exposure leads to oxidative stress, an imbalance between oxidant production and antioxidant defence in the body, which then leads to shortened relative telomere length (RTL) and reduced mitochondrial DNA copy number (mtDNAcn), ultimately leading to ageing and disease. By analysing the relationship among COEs, oxidative stress, RTL and mtDNAcn, we investigated the chain-mediating effects of oxidative stress and telomeres on mitochondrial damage and mitochondria on telomere damage in coke oven workers. A total of 779 subjects were included in the study. Cumulative COEs exposure concentrations were estimated, and the RTL and mtDNAcn of peripheral blood leukocytes were measured using real-time fluorescence quantitative PCR. Total antioxidant capacity (T-AOC) was measured to reflect the level of oxidative stress. The data were statistically analysed using SPSS 21.0 software and discussed using mediation effect analysis. After adjusting for age, sex, smoking, drinking and BMI, generalised linear model revealed dose–response associations between COEs and T-AOC, RTL and mtDNAcn, respectively. (Ptrend < 0.05). The results of chain-mediating effect showed that the proportion of the chain-mediating effect of “CED-COEs→T-AOC→ RTL→mtDNAcn” was 0.82% (β = −0.0005, 95% CI = [-0.0012, −0.0001]), and the proportion of the chain-mediating effect of “CED-COEs→T-AOC→ mtDNAcn → RTL ″ was 2.64% (β = −0.0013, 95% CI = [-0.0025, −0.0004]). After oxidative stress is induced by COEs, mitochondria and telomeres may interact with each other while leading further to potential bodily damage. This study provides clues to explore the association between mitochondria and telomeres. [Display omitted] •Interaction between mtDNAcn and RTL occurs after oxidative stress induced by COEs.•The first study of chain mediation between COEs, oxidative stress, RTL, and mtDNAcn.•A mediating effect model for COEs, oxidative stress, RTL, and mtDNAcn is proposed.